Muslim Minorities in the West: Visible and Invisible by Yvonne Yazbeck Haddad and Jane 1 Smith, eds. (New York and Oxford: AltaMira Press; 2002. 306 pages.) (American Journal of Islam and Society, 2003)
The Muslim diaspora, which has become established as a significant areaof publishing in the past 2 to 3 decades, is being charted by a number ofbooks and journals. This edited collection is a valuable addition to the literature,although specialists in the field will notice some degree of overlapwith existing sources.The book is divided into three sections exploring the Muslim experiencein America (seven chapters), Europe (three chapters covering France,Germany, and Norway), and areas of European settlement (five chapterscovering Australia, New Zealand, South Africa, and the Caribbean). Thebest way to view this book is to consider it a series of case studies examininghow Muslims in different contexts have moved from being temporary and peripheral individual sojourners to being, within their adoptedsocieties, generally well-established communities that have largely overcometheir internal differences and external structural barriers in order tobe publicly recognized as a part of multicultural and multi faith communitiesand societies. Many of the contributors believe that Muslim minoritiesare growing, dynamic, confident, and demographically "young" in most oftheir new societies, and that wherever they have established themselves,they have sustained their presence and thrived, sometimes in the face ofextreme hostility.This case study character has advantages and disadvantages. On theone hand, this reviewer found it extremely valuable to learn more aboutthe experience of some very specific minority groups, such as Sahelians inFrance, who are usually ignored and overshadowed in the literature by theoverwhelming Algerian-Moroccan presence in France. Likewise, with relativelylittle academic material available on Muslims in New Zealand, forexample, this book fills many of the academic gaps in the literature. Thefirst-hand accounts from previously unpublished sources were similarlyvaluable, and the chapter on establishing the Islamic Party in NorthAmerica constitutes an important documentary record. On the other hand,some chapters went over well-established ground, such as Turks inGermany. Specialists on Muslim minorities will find that some chaptersrepeat already well-known data and profiles oflslam in these contexts ...